Peran Keluarga dalam Meningkatkan Pendidikan Spiritual Anak - I Ketut Gunarta (Jurnal Penjaminan Mutu, 2016)
Family is the place in which the individuals are conditioned and prepared for the roles in the societies. Parents should do the preparation, preservation, direction, and be responsible for the spiritual and physical education and development of the children. They are also the motivators, advisors, as well as the friends of the children. Based on the roles the preservation of the cultural values and institutions is obtained in the societies. In educating the children informally, parents should play the roles in creating the harmony of the family, society, and with the God, through the practise of praying. The education can be done by: a) setting the good models to the children, b) emphasizing the importance of education, and c) controlling the children’s behaviors and habits.